2016
DOI: 10.18632/oncotarget.7943
|View full text |Cite
|
Sign up to set email alerts
|

Repeated observation of immune gene sets enrichment in women with non-small cell lung cancer

Abstract: There are different biological and clinical patterns of lung cancer between genders indicating intrinsic differences leading to increased sensitivity to cigarette smoke-induced DNA damage, mutational patterns of KRAS and better clinical outcomes in women while differences between genders at gene-expression levels was not previously reported. Here we show an enrichment of immune genes in NSCLC in women compared to men. We found in a GSEA analysis (by biological processes annotated from Gene Ontology) of six pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 27 publications
2
24
0
Order By: Relevance
“…Conversely, women have a higher incidence of non-small cell lung cancer (NSCLC) [309], but have been shown to have better prognoses than males [29]. It has been suggested that sex differences in NSCLC are due to immune differences, as female NSCLC patients exhibit significantly different immune gene set enrichment compared to males [310].…”
Section: Sex Differences In the Immune Systemmentioning
confidence: 99%
“…Conversely, women have a higher incidence of non-small cell lung cancer (NSCLC) [309], but have been shown to have better prognoses than males [29]. It has been suggested that sex differences in NSCLC are due to immune differences, as female NSCLC patients exhibit significantly different immune gene set enrichment compared to males [310].…”
Section: Sex Differences In the Immune Systemmentioning
confidence: 99%
“…The specific CRs have previously been found to play specific roles in specific cancer types. For example, the lung adenocarcinoma (LUAD) specific DNA methylation eraser APOBEC3F has been found to play important roles in the immune response in non–small cell lung cancer ( 39 ). Another LUAD–specific DNA methylation eraser, APOBEC3C , has been reported to be significantly associated with a decreased risk of lung cancer ( 40 ).…”
Section: Resultsmentioning
confidence: 99%
“…Predictions linking tumor-infiltrating neutrophils and plasma cells to overall survival were validated by microscopy and IHC in lung adenocarcinoma [6]. Several groups have successfully applied CIBERSORT for cell deconvolution in various complex tissues, including microarray studies of peripheral blood [53], lung biopsies [54], triple negative breast cancers [55], and glioblastomas [56], and RNA-seq analyses of endometrial cancers [57]. …”
Section: Cell Deconvolution For Solid Tumorsmentioning
confidence: 99%